Saline tidal flooding effects on Spartina densiflora plants from different positions of the salt marsh. Diversities and similarities on growth, anatomical and physiological responses - Di Bella, Carla Estefania (2014)
Spartina densiflora is a halophytic grass present in many salt marsh ecosystems where it dominates throughout topographical stress-gradients. This work aimed at studying diversities and similarities in ecophysiological responses of S. densiflora plants from two contrasting positions in the salt marsh. We simulated a natural tide by exposing plants of S. densiflora from upland and lowland sites of a salt marsh to saline intermittent flooding (9 h day−1) during 60 days. Responses in plant growth, biomass allocation, anatomy, ion regulation, and photosynthetic performance were assessed. Saline intermittent flooding caused changes in anatomical and morphological traits of plants from both sites associated with increased root aerenchyma and decreased mass allocation to leaf blades in relation to leaf sheaths, concomitant with reductions of blade size and changes in blade shape. Similar negative effects of saline intermittent flooding were found on physiological traits related to photosynthetic functioning of plants from both sites, like decreases in chlorophyll fluorescence, quantum efficiency and δ13C. However, lowland plants presented unaffected leaf length, better ion regulation (higher Cl− exclusion, higher K+ concentration, and lower Na+/K+ ratio), as well as later leaf senescence with respect to upland plants, when subjected to saline intermittent flooding. Accordingly, plant biomass production decreased by 15% and 32% for lowland and upland plants, respectively. These results indicate that plants of S. densiflora inhabiting in the lowland positions have a better acclimation capacity to the harsh environment imposed by the tide than plants from the upland.